STUDENTS’ DIFFICULTIES IN WRITING LINKING WORD - Alviona Dwi Marcella (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The objective of the research was to find out the students’ difficulties in writing linking word. The design of this research was descriptive method. The instrument of the research was linking word test by Buczko et.al (2017 :1-10) and questionnaire adapted from Pramadani (2021) about students’ difficulties. The result showed the fourth semester students in English study program have difficulties in writing linking word. The students lack knowledge about linking word because they difficult to understand the material so they difficult to identify linking word in the sentence. After that, the students also did not how much type of linking word and how to use it so they difficult to choose word and write the correct linking word that appropriate with the sentence. It is suggested the students: Students need the assistance to overcome the difficulties that they faced in writing linking word. The students should learn and practice to write linking word more to increase their ability in linking word. Key words: Linking Word, Students Writing Difficulties